The effects of fulvic acids and low-level laser therapy on orthodontic retention in rats - Jianmei Zhao; Qingmei Liu; Caifeng Zhang; Kuanshou Zhang; Pengfei Xin (BMC, 2024)
Abstract Background Shortening retention time and minimizing relapse rates are ongoing challenges in orthodontics. This study investigated the effects of natural fulvic acids (FAs) and low-level laser therapy (LLLT) on orthodontic retention in rats. Methods Seventy-two male Sprague-Dawley rats underwent mesial movement of the left maxillary first molar using a 50 g force via a nickel-titanium tension spring. After three weeks of movement, the rats entered the retention phase with retainer wires and were divided into four groups: Control (no intervention), FAs (80 mg/kg orally daily), LLLT (808 nm laser twice weekly), and FAs + LLLT (both treatments). Retainers were removed on days 7, 14, and 21 for a 3-day relapse assessment. Maxillary impressions were analyzed for relapse rates using 3Shape software, alongside histological and immunohistochemical evaluations of bone morphogenetic protein-2 (BMP-2) expression in periodontal tissues, with differences among groups analyzed using an ordinary two-way analysis of variance (ANOVA). Results The relapse rate decreased over time, particularly at 10, 17, and 24 days (p < 0.001). The FAs group did not significantly affect relapse rates compared to the control group (p = 0.084). In contrast, both the LLLT and FAs + LLLT groups significantly reduced relapse rate (p < 0.001), with no significant difference between these groups (p = 0.555). Histological examination revealed active osteoclasts on day 10, decreasing by days 17 and 24. The LLLT and FAs + LLLT groups showed less local cementum resorption and better periodontal fiber arrangement. All treatment groups significantly increased BMP-2 expression (P < 0.05) compared to controls. with LLLT and FAs + LLLT differing significantly from FAs (P < 0.001), though no difference was observed between LLLT and FAs + LLLT (P = 0.578). Conclusions FAs did not significantly reduce relapse rate with retainers, while LLLT effectively reduced relapse rates, showing no additional benefit from combining FAs with LLLT. Both FAs and LLLT increased BMP-2 expression in PDL fibroblasts but with no synergistic effect.